Pengaruh Kombinasi Pupuk Organik Cair (POC) Mikroorganisme Lokal (MOL) Nasi Basi dengan Mulsa Organik (Daun Ketapang (Terminalia catappa L) dan Pelepah Pisang (Musa sp.)) terhadap Intensitas Serangan Serangga Hama pada Tanaman Bayam Kakap (Amaranthus hybridus) - Desy Amanda Putri; Sonja Verra Tinneke Lumowa; Zenia Lutfi Kurniawati; Sri Purwati (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to determine the combination of Liquid Organic Fertilizer (POC) Local Microorganisms (MOL) stale rice with organic mulch (ketapang leaves (Terminalia catappa L) and banana stems (Musa sp.)) on the intensity of insect pest attacks on snapper spinach (Amaranthus hybridus) plants. The type of research used is experimental research. In this study, the population used was snapper spinach (Amaranthus hybridus). Observation data were analyzed using one-way ANOVA and continued with the Least Significant Difference (LSD) test at the 5% level. The results showed that the combination of POC-MOL stale rice with organic mulch ketapang leaves and banana stems had a significant effect on the intensity of pest attacks (p < 0.05). The intensity of pest attacks tended to decrease over the observation period, namely 7.34% (12 HST), 9.28% (17 HST), 6.70% (22 HST), and 5.00% (27 HST). The T4 treatment was the most effective combination in suppressing pest infestation compared to other treatments. Based on these results, it can be concluded that the combination of spoiled rice POC-MOL with organic mulch has the potential to be an environmentally friendly pest control method for spinach cultivation.